A STUDY ON THE OPERATIONS OF WOMEN SELF HELP GROUPS AND FRAMING OF MARKETING AND POSITIONING STRATEGIES FOR THEIR ETHNIC PRODUCTS & SERVICES - WITH SPECIAL REFERENCE TO SIVASAGAR DISTRICT, ASSAM (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
Women Self Help Groups are impending in a  big way where the spirit of their entrepreneurial  capabilities can be transparently witnessed.  This research attempted to lay down certain  management expertise to the pool of occupations  by the women self help groups by creating a  space of opportunities to them so that there  is a steady growth in the economy. Based  on the concept of bi-directional study and  purposive sampling design; fifty (50) Women  SHGs engaged in preparation of ethnic food  items and ten (10) organizations has been  considered by the researcher. The study area  has been confined to the Sivasagar District of  Assam. The study emphasized on the nature  of the SHGs operations and highlighted the  characteristics of the ethnic food items that can  be incorporated in a ready to eat ethnic lunch  basket. Competitiveness of the ethnic food items  of the SHGs in the competitive market has also  been put forward by the researcher through  an effective cost feasibility analysis. Suitable  marketing, positioning & branding strategies  of the ethnic food items and the selection of an  effective distribution channel for the SHGs has  also been proposed by the researcher. From the  study, it was inferred that the women members of  the SHGs can enter into the competitive market  with a boom and with effective promotional  & positioning strategies, the ethnic food items  of Assam do posses the capacity of giving stiff  competition to the commercial food items and  can create a niche in the market and thus, can  also attain a national presence.
Keywords: Women Self; strategies; competition